THE EFFECTIVITY OF RELIGIOUS VALUES FOR THE EMPOWERMENT OF WOMEN TOWARDS THE WORKING BEHAVIOR IN SYARIAH ECONOMY PERSPECTIVE (EMPIRICAL STUDY OF NIGHTCLUB IN MAKASSAR) - Aisya, Sitti; Hamzah, Natsir; Abdullah, Wahyuddin; AR, Moh Sabri (Jurnal Diskursus Islam, 2020)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; tab-stops: 45.8pt 91.6pt 137.4pt 183.2pt 229.0pt 274.8pt 320.6pt 366.4pt 412.2pt 458.0pt 503.8pt 549.6pt 595.4pt 641.2pt 687.0pt 732.8pt;">Women are one of the most important resources for the sustainability of national development, they are a potential asset as the subject of development. These socio-economic problems trigger one of the reasons for women to work both as women with a single status and as married (mother and wife). The choice of THM as the last choice for women can provide maslahah for their family life. Makassar City is one of the cities with a significant THM development. Along with the development of the city of Makassar as a Metropolitan city towards the vision of a World city. However, working in a nightclub is a choice or a job option when faced with a situation. Women who work in nightclubs do not lose sight of the beliefs they have, the desire for a sufficient income and the lifestyle that triggers the work.